2012
DOI: 10.1155/2012/187965
|View full text |Cite
|
Sign up to set email alerts
|

Seven Capital Devices for the Future of Stroke Rehabilitation

Abstract: Stroke is the leading cause of long-term disability for adults in industrialized societies. Rehabilitation's efforts are tended to avoid long-term impairments, but, actually, the rehabilitative outcomes are still poor. Novel tools based on new technologies have been developed to improve the motor recovery. In this paper, we have taken into account seven promising technologies that can improve rehabilitation of patients with stroke in the early future: (1) robotic devices for lower and upper limb recovery, (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 93 publications
(112 reference statements)
1
79
0
6
Order By: Relevance
“…Rehabilitators should train subjects with amputation to progressively optimize gait features such as stability, efficiency, and functioning by making a safe choice about WS. Our study, together with previous ones [1,9,27], also showed that the use of a single triaxial accelerometer (i.e., a low-cost, wearable, and easy-to-use device [44]) can provide useful quantitative and objective information about important gait features. The common walking tests performed in clinics on subjects with amputation, such as the 10 m walking test or the 6 min walking test [45], just measure speed of walking without providing information about the optimization of other important aspects of gait.…”
Section: Discussionsupporting
confidence: 72%
“…Rehabilitators should train subjects with amputation to progressively optimize gait features such as stability, efficiency, and functioning by making a safe choice about WS. Our study, together with previous ones [1,9,27], also showed that the use of a single triaxial accelerometer (i.e., a low-cost, wearable, and easy-to-use device [44]) can provide useful quantitative and objective information about important gait features. The common walking tests performed in clinics on subjects with amputation, such as the 10 m walking test or the 6 min walking test [45], just measure speed of walking without providing information about the optimization of other important aspects of gait.…”
Section: Discussionsupporting
confidence: 72%
“…Patients' recovery and progress can be monitored by the sharing of information electronically by tablet computers with the community rehabilitation teams [51]. Previous pilot studies of iPad-based home rehabilitation have shown high satisfaction rates as patients felt that the intervention is modern, engaging and cutting edge [30].…”
Section: Patients' Acceptability Of Ipad-based Rehabilitation and Selmentioning
confidence: 99%
“…The future of stroke rehabilitation increasingly includes technological approaches [35]. In approaching the application of new technologies, a collaborative approach is required between researchers and clinicians [34].…”
Section: The Challenge Of Implementing Evidence Based Practice In CLImentioning
confidence: 99%